A Translation Study of Manipulation Speech Acts in WandaVision and Doctor Strange in the Multiverse of Madness - Kusumaningrum, Dyah Ayu; Nababan, Mangatur Rudolf; Wibowo, Agus Hari (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
Manipulation is a form of utterance that has hidden intention (illocutionary force), which is included in a branch of pragmatics. When performing manipulative speech, the speakers influence their victims’ minds so that they can respond the way the speakers want. Therefore, the speakers use manipulation strategies to achieve their intentions. This study aims to identify the manipulation strategies used by the characters in the WandaVision drama series and Doctor Strange in the Multiverse of Madness movie. It also examines the translation aspects of the subtitles from English to Indonesian based on translation techniques theory by Molina and Albir (2002), as well as the rule of translation quality assessment made by Nababan, et al (2012). Data analysis in this study uses the document analysis method and Focus Group Discussion involving three raters who are experts in pragmatics and translation theories. The results show that the characters in WandaVision drama series and Doctor Strange in the Multiverse of Madness movie used all 13 manipulation strategies, whose theory was initiated by George K. Simon (2010). Meanwhile, in terms of translation, the translator chose to be more orientated towards the target language, as proved by the dominance of techniques used, such as established equivalence, variation, implisitation, and paraphrase. The overall quality of the translation results is considered very good by the raters, and there are only two types of translation shifts found. The study hopes to serve as a reference for manipulation speech acts, offering valuable insights regarding the strategies to do manipulation and how the topic of manipulation in fictional works can be studied through a translation perspective.